Restoration of decorative glazed ceramic from Morocco: Technical replicas - Claire Dehon; Mouhssin El Halim; Nathalie Fagel; Lahcen Daoudi; Catherine Cools; Valérie Rousseau; Meriam El Ouahabi (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Historical buildings in Morocco feature decorative glazed ceramic tiles known as zelliges, which often require restoration due to degradation. Reproduced tiles frequently lack the original physico-chemical properties, leading to various conservation issues. This study examines the zelliges from the Saadian Tombs and El Badi Palace (16th-17th centuries) to develop compatible replicas. Samples were prepared using clay from Fès, fired from 600°C and 900°C, and analyzed for shrinkage, weight loss, and water absorption. The mortars were also analyzed. A high water absorption was observed, enhancing the adhesion between the zellige and the mortar.